Fic livro: fandom e polissistema literário - Utzig, Ingrid Lara de Araújo (Universidade Estadual Paulista, 2022)
The fanfiction A Lenda de Fausto, written by Samila Lages, was transformed into a novel by Multifoco publisher in 2011. Based on the considerations of Henry Jenkins, Anne Jamison, Néstor Canclini, Régis Debray, Giselle Beiguelman and other theorists, this research aimed to discuss the mobility of Samila's work, whose fluctuation occurred between four platforms: Nyah!, a fanzine, Samila’s blog and the book. The intention was to understand the paths that preceded the publication, going through the creation, production, reproduction, circulation, reception, diffusion and publishing processes of A Lenda de Fausto. In such way, it was noticed that the fanfiction has specific aesthetic (im)possibilities provided by the digital environment, since it explores some potentialities/limits of Nyah’s interface and it unfolds in spin-offs, because in addition to A Lenda de Fausto, there is the prequel Relatos da Queda and the sequel O Trilo do Diabo. It was intended to observe the poetic(s) in the construction of this object and how Samila appropriates different strategies in order to establish herself as a reknowned writer inside and outside the otaku microcosm. The objectives of this thesis were focused on investigating whether the fandom(s), virtual communities organized in the redefinition of franchises and cultural industry contents, with rules gathered around a non-passive reception, in a model of productive consumption, constitutes itself as a culture system. To debate these dynamics, it was used the polysystems’ theory, by Even-Zohar (2017). The second objective was to propose that A Lenda de Fausto, in its materiality displayed on Nyah!, establishes itself as e-literature, despite the fact that it is not a common premise for fanfiction as a genre, and how the practice undertaken on the platform was discontinued and even erased from the exordial context during the transition to later mediums. The third objective was to notice how the fandom’s literary factors put Samila into the literary polysystem through the transition to the printed editorial market, which generated a metamorphosis of her status - from ficwriter to author -. Finally, it was sought to understand how this double existence of Samila occurs, in systems with different behaviors. The thesis defended was that A Lenda de Fausto highlights the intersection of different polysystems through the change of materiality: as fanfiction, a series of factors led to the legitimization in fandom. As a novel published in a book, it began to have other forms of circulation and wider audiences, generating a double layer of consecration: within the fan community and in the literature of Amapá.